Integrating 3D printing into an early childhood teacher preparation course: Reflections on practice. Issue 1 (2nd January 2017) - Sullivan, Pamela; McCartney, Holly
ABSTRACT: This reflection on practice describes a case study integrating 3D printing into a creativity course for preservice teachers. The theoretical rationale is discussed, and the steps for integration are outlined. Student responses and reflections on the experience provide the basis for our analysis. Examples and resources are provided, as well as a discussion of lessons learned.